PENGARUH PENGETAHUAN, SOSIALISASI DAN SANKSI PERPAJAKAN TERHADAP KEPATUHAN WAJIB PAJAK UMKM PASAR DESA PENGALANGAN - Rosvita Debora Mansawan; Muninghar Muninghar (Jurnal Ekonomi, Bisnis dan Social, 2024)
This study aims to examine and determine the effect of profitability and good corporate governance on earnings quality. The population in this study is the Pulp sub-sector tbk manufacturing company. & Paper for the period 2018 to 2020 with a total of 24 company observations. The samples used in this study were 18 manufacturing companies in the Pulp sub-sector. & Paper. The sample selection method used was purposive sampling. The research data analysis model uses multiple linear regression analysis. The proxy used to measure the quality of company earnings is by calculating the value of discretionary accruals. The results showed that profitability had a positive effect on earnings quality, while good corporate governance proxied by institutional ownership and audit committees had no effect on earnings quality.